STAREA DE SĂNĂTATE ORO-DENTARĂ LA UN LOT DE COPII CU SINDROM DOWN - Carmen Savin; Adriana Bălan; Ciprian Cîrcu; Eugeniu Mihalaș; Ana Petcu; Laura Gavrilă (Romanian Dental Association for Education, 2017)
Down syndrome is an autosomal chromosomal abnormality that affects the population in varying proportions. Aim. To establish the degree of health and oro-dental diseasses, as well as the need for treatment in a group of children aged between 6 and 12 years, diagnosed with Down syndrome. Material and Methods. The study was conducted on a group of 25 children with Down syndrome aged 6 to 12 years. As an indicator of the dental treatments that each child has benefited from up to the time of examination, was used the MNI index; as an indicator of the restorative treatment received by a child was used the RI index. The level of oral hygiene was assessed based on the OHI-S Index and the quantification of the amount of the bacterial plaque was assessed with the PI index. Results: The prevalence of caries in the study group was 92%. The value of RI index was 0.19 and of the MNI 0.26. The dmft / DMFT values were significantly correlated with OHI-S and PI values. Conclusions: The study revealed a high incidence of oral health problems among children with Down syndrome.